Análise da prática profissional de enfermeiras obstétricas: transformá-la para conhecer a realidade - Regiane Prado Ribeiro (2020)
In the field of obstetrics, advances are identified in professional regulation, education, and qualification, in childbirth and birth care humanization, among other aspects related to professional practice. However, immense challenges remain to provide safe conditions for birth in the country. In the Brazilian health system, the so-called biomedical model still prevails as control of obstetric and neonatal care. In the teaching hospital scenario, professional disputes and legitimacies are even fiercer, because, in this setting, residency and undergraduate medicine and nursing professors and students devoted to childbirth and birth care gather to consolidate their professional qualification. The general objective of this study was analyzing obstetric nurses’ professional practices at a maternity hospital in a public university hospital located in Belo Horizonte, Minas Gerais, Brazil. This is an intervention research with a qualitative approach in which the methodological theoretical framework of Institutional Analysis was used according to its socioclinical orientation. For data production, 4 socioclinical meetings were held, which had the participation of 15 nurses. Also, semi-structured interviews were conducted with 6 managers, some of whom still work and others have worked in the maternity hospital. Another tool for data collection and generation was the researcher’s institutional diary. The survey covered the period from November 2018 to February 2020. The results encompass the difficulties faced by obstetric nurses during their entry into the maternity hospital, the conflicts of action with management and the medical team, in addition to the daily challenges in professional practice, such as the inadequate nursing staff sizing and the work processes. Among the reported difficulties, the fact that obstetric nurses are unable to work more effectively along with parturient women in a continuous and humanized care stands out, due to the imposition of institutional routines and administrative activities, which absorb most of their time. The socioclinical meetings made it possible to analyze the nurses’ libidinal, ideological, professional, and organizational implications, bringing to the fore their struggle for professional autonomy and recognition, as well as the various institutions that permeate their professional practice, such as medicine, teaching, management, and nursing itself. By acknowledging such institutions, we could look for strengthening strategies and transformative actions needed to consolidate the obstetric nurses’ professional practice. Thus, as one of the products of this intervention research, strategic planning was adopted as a tool capable of contributing to the organization and systematization of actions proposed by the group, to team shared accountability, to work continuity, and above all to the advancement of knowledge production in obstetric nursing within the teaching hospital scenario.